2013
DOI: 10.1093/geronb/gbt052
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Subjective Wellness Among the Old-Old: Implications for the "Fourth-Age" Conception

Abstract: At old-old age, the results point to reduced predictability of subjective wellness by factual dysfunction. This finding supports the fourth-age model. Still, researchers should consider an alternative interpretation, by which increasing independence between factual and subjective indicators is protective, rather than debilitating, among old-old people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Our findings that independence in activities of daily living was not significantly related to frail older people’s life satisfaction were more surprising, as many prior studies have found a relationship between independence in ADL and life satisfaction (Bowling et al , 1993 ; Hillerås et al , 2001 ). Additionally, another study showed that dependence in ADL predicted subjective well-being among people at old-old age (Shmotkin, Shrira, Eyal, Blumstein & Shorek, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that independence in activities of daily living was not significantly related to frail older people’s life satisfaction were more surprising, as many prior studies have found a relationship between independence in ADL and life satisfaction (Bowling et al , 1993 ; Hillerås et al , 2001 ). Additionally, another study showed that dependence in ADL predicted subjective well-being among people at old-old age (Shmotkin, Shrira, Eyal, Blumstein & Shorek, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while most of the 12 articles conceive of resilience in a similar way as laid out in the present study-as the capacity to recover from or adapt to challenging circumstances (e.g., Masten, Best, & Garmezy, 1990)-the potential value of resilience in shaping aging-related changes was not examined. Of the studies on resilience, several articles were guided by resilience as a conceptual framework (e.g., Emlet et al, 2013;Frederickson-Goldsen et al, 2013;Kotter-Gruhn & Hess, 2012;Pitzer & Fingerman, 2010) or a resilience theoretical perspective (Emlet et al, 2011), while others were concerned with resilience as a physical outcome (Resnick et al, 2011;Shmotkin et al, 2013), or were equated with subjective quality of life (Hildon et al, 2010). Only one article used a resilience scale (the Connor-Davidson resilience scale), which was included only as a control variable (Wolinsky et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Very old individuals' adaptational abilities are immensely challenged by various agerelated losses and increased vulnerability (Chui et al, 2015;Haugan et al, 2013b;Ihle et al, 2017;Schilling et al, 2013;Shmotkin et al, 2013;Wettstein et al, 2015). At the same time, the need for adaptation becomes even more crucial for the same reasons (Ihle et al, 2017;Shmotkin et al, 2013). Thus, some authors raised concerns regarding whether very old age curbs this ability (Hansen & Slagsvold, 2012;Nakagawa et al, 2018;Palgi, 2013).…”
Section: Ability To Adaptmentioning
confidence: 99%
“…Other aspects of health were also seen as closely connected to well-being. For instance, psychological well-being was regarded an integrative factor of one's physical health (Zaslavsky et al, 2014), and perceived health was used as an indicator of well-being (Tomás et al, 2012;Shmotkin et al, 2013). However, others did not equate perceived health and wellbeing; they instead used perceived health as an explanatory variable for well-being (e.g., Neubauer et al, 2017;Ng et al, 2017), reflecting an inconsequence in how health-related concepts are considered and used in relation to well-being.…”
mentioning
confidence: 99%